PENGENALAN DAN PELATIHAN MAPLE GUNA MENINGKATKAN HASIL BELAJAR DAN PEMAHAMAN MATEMATIKA - Dian Agustina; Etis Sunandi; Herlin Fransiska (DHARMA RAFLESIA, 2018)
The training and introduction of MAPLE is aimed to improving SMA Negeri 8 Kota Bengkulu students' logic and analysis ability to solve math problems. The steps taken are to prepare syllabus and MAPLE training material module that can be used as reference in the implementation of coaching, then carry out training for one month. From the pre-test and post-test results it can be concluded that there is a significant difference from the learning result before and after knowing and using MAPLE. The average post-test score is much greater when compared with the student's pre-test score. Paired sample testing gives a t-value of 24,079 with p-value 0.000. It can be concluded that the average pre-test and post-test values are significantly different. This means that the introduction and training of MAPLE in SMA Negeri 8 gives a real influence on students' mathematics learning outcomes. Keywords: MAPLE Training, Mathematics